Probabilistic weather forecasting using Bayesian Model averaging: the case of Sagcot Regions - Joel, Emmanuel (Mzumbe University, 2024)
A dissertation submitted in partial/ fulfillment of requirements for award of the Degree of Master of Science in Applied Statistics of Mzumbe University